Clonal Hematopoiesis and Risk of Atherosclerotic Cardiovascular Disease - Jaiswal, Siddhartha; Natarajan, Pradeep; Silver, Alexander J; Gibson, Christopher J; Bick, Alexander G; Shvartz, Eugenia; McConkey, Marie; Gupta, Namrata; Gabriel, Stacey; Ardissino, Diego; Baber, Usman; Mehran, Roxana; et al. (The New England journal of medicine, 2017)
The development of clonal hematopoiesis with increasing age was associated with nearly a doubling in the risk of coronary heart disease, along with an increase in coronary calcifications, possibly due to heightened production of inflammatory markers.